Self-efficacy in pedagogical practices of trainee teachers during the pandemic - Gallardo-Contreras, Nilda Ester; Nocetti de la Barra , Alejandra Viviana; Muñoz-Soto, Maurine Constanza (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2023)
The objective of this article is to analyze the teaching self-efficacy in pedagogy students from two universities in southern Chile who were carrying out intermediate and professional practice in the context of the COVID-19 pandemic. The research was approached through the quantitative paradigm and had a cross-sectional character with a descriptive scope. A non-probabilistic sample of 150 teachers in training was selected. The results show that students feel capable of teaching all students in adverse contexts. It is concluded that, given the health emergency, teachers in training increased teaching self-efficacy, with virtual teaching being a time of intense professional learning.